Prioritize the factors affecting on development of ecotourism villages of Barzok district- kashan by Combining DEMATEL and ANP Methods - Mohsen Shaterian; Sedigheh Kiani; Yones Gholami; Zahra Montaseri (تحقیقات کاربردی علوم جغرافیایی)
A most important part of the world’s tourism activities is based on the use of nature and areas having valuable natural potentials. one most considered in this regard the aim of this research is priorititing the affecting factors on development of ecotourism in villages of Barzok district. As a need for tourism planning. The research method is descriptive – analytical And Results are combined using ANP and DEMATEL methods. MATLAB and Super Decisions software used for Results analysis. The results show that among the 17 criteria participate of local and regional investors and giving respansibilitis of Assignment, Tourism organizating and managment to local people have the highest score and stand in the first rank. Visiting tours, especially during Rose water production and during growing season of Medicinal Plants and the use of local and interested people as a tour leader and stand the second and third respectively.